Accounting Learning Model Following ICT Development to Be Sustainable - Listiadi, Agung (International Journal of Scientific Research and Management (IJSRM), 2024)
The discovery and advancement of information technology in the form of computers is something that is very important and fundamental. Various types of computers have occupied their position in society. The computer not only helps carry out work, but changes work procedures and at the same time creates new challenges and problems in the environment. The 21st century is known as the century of globalization and the century of information technology. In this century there have been major changes in technological systems, including information technology. The proper use and utilization of information technology in the form of computers and the internet in education is able to overcome the emergence of obstacles and distractions for students or teachers in the teaching and learning process. The use of information technology must be based on the right selection so that it can enlarge the meaning and function in supporting the success of the teaching and learning process. The digital classroom connects teachers and students with the digital resources and tools needed to collaborate in the classroom and around the world. Schools of the future are schools that are based on ICT (Information Communication and Technology) in real terms.